2019
DOI: 10.1002/ajhb.23322
|View full text |Cite
|
Sign up to set email alerts
|

The environment contribution to gender differences in childhood obesity and organized sports engagement

Abstract: Objective This study aims to analyze gender‐specific associations between sports activity outside of school and obesity, observing to what extent the local built environment contributes to the patterns found. Methods A total of 2253 children aged 6.0‐11.0 years were assessed: 49.3% girls and 50.7% boys. Children's weight and height were measured, age and sex‐specific BMI cut‐off points were used to define normal vs overweight/obesity. Children's organized sports (OS) activity was assessed by questionnaire, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…Such differences are more evident as these individuals reach adolescence, although there is some evidence pointing to the differences in physical activities between younger children. A Portuguese study carried out with students aged 6–11 years identified girls as having higher levels of excess weight alongside practicing lower levels of organized sports outside of school compared to boys (Nogueira et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Such differences are more evident as these individuals reach adolescence, although there is some evidence pointing to the differences in physical activities between younger children. A Portuguese study carried out with students aged 6–11 years identified girls as having higher levels of excess weight alongside practicing lower levels of organized sports outside of school compared to boys (Nogueira et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors contribute to childhood and adolescent obesity, including amongst others gender, biology, geographical and socio-economical aspects 72 73 74 . Non-communicable diseases, such as overweight and obesity are largely preventable.…”
Section: Adipose Tissuementioning
confidence: 99%
“…Physiologically, obesity is caused by a long-term imbalance between energy intake (eating) and energy consumption (physical activity). Physical activity can be important in weight control (Fogelholm and Kukkonen-Harjula, 2000), and different opportunities for organized sports in boys and girls can also contribute to sex differences in childhood obesity (Nogueira et al, 2019). Additionally, other factors than eating and physical activity have been suggested to contribute to the obesity epidemic (McAllister et al, 2009).…”
Section: Introductionmentioning
confidence: 99%